Custom Made Low-Cost Optoelectronic Flex Sensor and Its Parameterization - Pozzobon, Luiza; Guerra, Rodrigo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
The use of flex sensors to evaluate the amount of bending of certain materials has many applications that range all the way from music creation to prosthetic devices. However, commercially available flex sensors are expensive and especially difficult to afford in developing countries, among which we cite as an example Brazil. Their high cost precludes their experimentation and usage in systems that demand a high number of sensors. With this thought in mind, this paper presents the design of a low-cost optoelectronic sensor, constructed with readily available simple materials, such as a coil spring, a LED and an LDR sensor. Parameterization tests were performed to evaluate its functioning limits. It can be concluded that the reflective nature of the spring assists with the propagation of the light projected inside it, ensuring that the illumination is not interrupted early in the bending motion. The optimal sensor length is of 3 cm since it presented the most stable and consistent results.